Programa nacional de municipalização do turismo : sustentabilidade e descentralização das políticas de turismo no recém criado município de Guapimirim, RJ - Silva, Luiz Fernando Saraiva da (2009)
The aristocratic tourism reached in Brazil around 1920. After this phase, in the middle of the 1950 s, projects oriented by marketing induced tourism started to exist in the country they continue in the military governments but they did not advance. A new process came to the country, supported by the Federal Constitution of 1988, which determined the ideal of the public policies decentralization through the municipalization the emergence of the local power. This new phase was inaugurated at the President Collor s Government, when Brazil under world markets pressure and due to a politic & economical project that saw itself as modernizing - drowned in the globalization. Under such influence, the PNMT - Programa Nacional de Municipalização do Turismo (National Programme for Tourism Municipalization) was created at the end of 1993. Essentially, the PNMT wagered on a formal & technocratic training of instructors and multipliers, from then responsible for problems solving to the local / city / town, for such problems opposed to the tourism as a sustainability alternative. Under the influence of the above-referred Constitution, Guapimirim became an autonomous city at 1990, based on a political speech, which situated the tourism as the main development alternative. Elected by the Federal Government as a Capital City for the Tourism Development, Guapimirim received at 2002 the strategies definition workshops for the achievement of the local tourism. Meanwhile, the tourism in Guapimirim stayed incipient. Forced by the global market speed which turns around the public policies and due to the political-administration lack of preservation usually (and culturally) practiced in Brazil, the own PNMT disappeared so quickly as it originated.